Rumex and polygonum in colombia (1946)
Rumex and Polygonum, of the family polygonaceae, occur in some abundance both in Colombia and in the United states, and this paper is an attempt to correlate a study of the Colombian plants with what has been observed in the United states. Through the courtesy of Dr. William R. Maxon, Curator, the facilities of the United states National Herbarium have been made available, and this work has been financed by the Wisconsin Alumni Research Foundation of Madison, Wisconsin. The writer's collections and field observations were made in Colombia from March to December, 1944, during such times as would not interfere with his work for the Colombian Cinchona Mission. Mr. E. P. Killip, Dr. F. R. Fosberg and Mr. Joseph Ewan have given me the benefit of their experience in South American botany to make a number of helpful suggestions.